Psalm 121: Yahweh's protection against mythological powers - Mare, Leonard P. (Old Testament Essays, 2006)
Psalm 121 is a beautiful poem that aims to create trust in Yahweh. The psalmist utilizes various stylistic features to emphasize the fact that Yahweh will protect him or her from all enemies. The polemical traits of Psalm 121 lead to the conclusion that the enemies in the psalm are equal to mythological powers. These powers threaten the life of the psalmist, creating fear and anxiety in his or her heart. The psalmist then uses the creation tradition to ensure the righteous of Yahweh's encompassing, everlasting, comprehensive protection in the face of any and every danger or threat. No enemy, not even mythological powers need to be feared, when the righteous trust in Yahweh, the maker of heaven and earth.
free